1958
DOI: 10.4141/cjps58-064
|View full text |Cite
|
Sign up to set email alerts
|

THE INHERITANCE OF RESISTANCE TO BACTERIAL WILT (ERWINIA TRACHEIPHILA (E.F.SM.) HOLLAND) IN CUCUMBER

Abstract: The inheritance of resistance to bacterial wilt in cucumber was studied in the cross Marketer x P.I. 200818 by observing the reaction of P1, F1, F2 and B1 seedling populations in the greenhouse to inoculations with Erwinia tracheiphila (E.F.Sm.) Holland. The results show that resistance to bacterial wilt in the P.I. 200818 cucumber is due to a single dominant gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1965
1965
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Ellis and Halst; Barnes and Epps 1952]. PI 200818 originating from Myanmar is resistant to bacterial wilt [ Erwinia tracheiphila (Smith); Nuttall and Jasmin 1958]. Cucumber germplasms from Asia are considered to be important sources for disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Ellis and Halst; Barnes and Epps 1952]. PI 200818 originating from Myanmar is resistant to bacterial wilt [ Erwinia tracheiphila (Smith); Nuttall and Jasmin 1958]. Cucumber germplasms from Asia are considered to be important sources for disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Steadman (personal communication) observed that 'County Fair', resistant to beetle feeding, was highly sus ceptible to the disease. Resistance to E. tracheiphila is best provided through the ac tion of the Bw gene in cucumbers (37). No high resistance to E. tracheiphila has been identified in C. melo; only 1 cultivar, 'Bur rell's Gem' with 20% plant survival, was found among 250 inoculated melon cultivars (42).…”
Section: Germplasm Sources Of Resistancementioning
confidence: 99%
“…The United States Department of Agriculture (USDA) Germplasm Resource Information Network ( ; accessed on 17 September 2021) has a large collection of melon (>2000 accessions) and cucumber (~1300 accessions), which have played critical roles in US melon and cucumber breeding by providing important disease resistance sources. However, limited work has been done to screen the melon and cucumber germplasm for resistance to bacterial wilt [ 20 , 21 ], which is the first step in developing BW-resistant varieties [ 22 , 23 ]. Thus, the objective of this study was to screen melon accessions for resistance to bacterial wilt disease in response to mechanical inoculation by bacterial wilt pathogen, Erwinia tracheiphila .…”
Section: Introductionmentioning
confidence: 99%